Razvojne možnosti naselij na depopulacijskih območjih glede na starostno sestavo gospodinjstev - Benkovič Krašovec, Monika (Geografski vestnik, 2005)
The aim of this research was to find out advantages, disadvanteges and development possibilities of eight settlements (Ostrožno Brdo, Tatre, Krplivnik, Ocinje, Grdina, Pohorje, Jagršče, Šentviška Gora) in different Slovene depopulation areas (Brkini, Goričko, Haloze, Idrijsko hribovje). A special emphasis was placed on the study of households as basic socioeconomic units, on which future development of settlements is based. The households were classified into viable, potentially viable and non-viable, subject to the age structure of their members.
Keywords: podeželje; rural area; geografija naselij; poselitev; demografski razvoj; depopulacija; regionalni razvoj; Slovenia; Slovenija